Isolation and partial characterization of globulin from Cassava (Manihot Esculenta Crantz) tubers - Barbosa, May Roldan
Soluble globulin was isolated using an extraction buffer (0.4 M NaCl in 35 mM potassium phosphate buffer, pH 7.6 with 0.02 percent Na azide). The isolated globulin was subjected to solubility tests with different NaCl concentrations. It has the highest solubility in 1.25M NaCl (1.09 percent) but no significant differences existed among the NaCl concentrations by analysis using one-way ANOVA at a = 0.05. Three major bands existed at 1.00M NaCl dissolved globulin with molecualr weight range of 28 -33kDa, 38-43kDA and 65-70kDa relative to BSA. Two of these bands (38-43kDA and 65-70kDa) were observed in 0.50M and 75M NaCl soluble globulin. The 1.25M and 1.50M and NaCl concentrations gave a single band (28-33kDa) each while no clear bands in other NaCl concentrations were observed., Amino acid analysis revealed glutamic acid (12.09 percent) as the most abundant amino acid component of cassava globulin (Nine (9) essential amino acids were present. Of these nine, lusine (10.50 perent) is the most predominant. Cystine (0.39 percent) has the lowest percentage followed by methionine (1.76 percent).
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Cassava; Manihot Esculenta Crantz